1998
DOI: 10.1074/jbc.273.48.32049
|View full text |Cite
|
Sign up to set email alerts
|

DNA-dependent Activation of the hMutSα ATPase

Abstract: ATP hydrolysis by MutS homologs is required for function of these proteins in mismatch repair. However, the function of ATP hydrolysis in the repair reaction is controversial. In this paper we describe a steady-state kinetic analysis of the DNA-activated ATPase of human MutS␣. Comparison of salt concentration effects on mismatch repair and mismatch-provoked excision in HeLa nuclear extracts with salt effects on the DNA-activated ATPase suggests that ATP hydrolysis by MutS␣ is involved in the rate determining s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
60
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 46 publications
10
60
4
Order By: Relevance
“…Homology between the MutS homologs is largely based upon a highly conserved Walker-A/B adenosine nucleotide and magnesium-binding domain (3,9). Although aspects of ATP binding/hydrolysis by the bacterial and yeast MutS homologs have been examined (15)(16)(17), more comprehensive studies of the human hMSH2-hMSH6 heterodimer have demonstrated coupled ATP and DNA binding properties as well as an intrinsic ATPase activity that is stimulated by mispaired DNA (1,2,5,18,19). A defining observation is that binding to mismatched DNA by MutS and hMSH2-hMSH6 is abolished in the presence of ATP (1,10,20).…”
Section: Mismatch Repair (Mmr)mentioning
confidence: 99%
See 4 more Smart Citations
“…Homology between the MutS homologs is largely based upon a highly conserved Walker-A/B adenosine nucleotide and magnesium-binding domain (3,9). Although aspects of ATP binding/hydrolysis by the bacterial and yeast MutS homologs have been examined (15)(16)(17), more comprehensive studies of the human hMSH2-hMSH6 heterodimer have demonstrated coupled ATP and DNA binding properties as well as an intrinsic ATPase activity that is stimulated by mispaired DNA (1,2,5,18,19). A defining observation is that binding to mismatched DNA by MutS and hMSH2-hMSH6 is abolished in the presence of ATP (1,10,20).…”
Section: Mismatch Repair (Mmr)mentioning
confidence: 99%
“…An argument against the Molecular Switch model was recently forwarded by Blackwell et al (5,19) and is based on the following observations: (i) a similar dissociation constant (k d ) between hMSH2-hMSH6 and mismatched DNA in the presence or absence of ADP; (ii) plasmon resonance spectroscopy demonstrating ADP-induced release of hMSH2-hMSH6, which was prebound to mismatched DNA in the absence of nucleotide (albeit Ͼ10-fold slower than ATP-induced release); (iii) an ATPase "salt profile" that appeared similar to MMR and mismatch-provoked excision reactions in vitro, and 4.) a "significant" DNA length-dependent increase in the k cat⅐DNA for the ATPase.…”
Section: Mismatch Repair (Mmr)mentioning
confidence: 99%
See 3 more Smart Citations